APPLICATION OF COGNITIVE BEAHVIORAL THERAPY FOR TREATMENT OF SEXUAL OCD - Rana, Madiha (Journal of Pakistan Psychiatric Society, 2024)
Our population growth problem is manifesting itself in physical and mental health issues which are growing at a steady pace.  Viruses have various mutations, so is the case with mental health issues. As a clinical psychologist and practitioner, I observe a wide range of such variations. Mostly, individuals with obsessive compulsive disorder (OCD) can be characterized within the domain of fear due to contamination from dirt, fear of death, religious beliefs etc. There is a considerable group of people within those who also deal with unwanted sexual thoughts, impulses and illusions. The cultures that are conservative in nature have people who  hold certain kind of beliefs or intrusive thoughts which is considered a taboo [1].  People don’t want to talk about it due to conditioning. As opposed to, if someone shares such thinking, the society at large, and the close associates such as friends and family stigmatize them, they are made to feel guilty and often labeled as a “wrongdoer.” This is as a result of lack of awareness [2].